Psichologiniai kai kurių darbo aspektų tyrimai mokslinėje techninėje bibliotekoje - Šimkūnienė, Leontina (Knygotyra, 1976)
The present article deals with the basic criterions of satisfaction that is experienced from work by the workers of the scientific technical library of a scientific research institute.The workers of this library filled in special forms that were prepared by paying the main attention to material and–basically–to psychological aspects.The results show that psychological motives are the principle motives of satisfaction got from work in our collective. The workers of our library experience less satisfaction in business contacts.In conclusions emphasize the necessity for the librarians of such libraries to be aware of the scientific subjects carried out in the institute and to study continuously interests and needs of the readers-specialists.